Modeling and Energy Generation Evaluations of Large-Scale Photovoltaic Plants Equipped With Panel-Level DC Optimizers - Wang, Qin; Le, Lingling; Li, Dahu; Ai, Xiaomeng; Fang, Jiakun; Yao, Wei; Wen, Jinyu (Frontiers in Energy Research, 2022)
The distributed maximum power point tracking (DMPPT) technology, based on a DC optimizer (DCO, a DC/DC micro-converter) for each single photovoltaic (PV) panel, is one of the most popular solutions to mitigating the waste of solar energy when suffering mismatch conditions. However, the trade-off between the additional costs of deploying the panel-level power electronic equipment and the improved generation benefits of a large-scale PV plant (LPP) remains to be further studied. This study presents a static modeling method for the DCO-based distributed LPPs to study the long-term energy generation characteristics based on historical hourly weather data and then evaluate the economic benefits. The operational characteristics of the PV strings equipped with series-connected DCOs for three different topologies (Boost, Buck, and Buck-boost) are investigated, and then the control strategies for the PV-DCO generation units are proposed to maximize the energy generation of LPPs under frequent mismatch conditions. Different mismatch scenarios caused by the panel aging, geographical location settings, and the partial shading in PV arrays are simulated in the model. Six typical centralized or distributed PV plant configurations are carried out for comparison in case studies, to explore the generation characteristics and the advantages of energy production for the DCO-based distributed LPPs. Besides, the Levelized cost of energy (LCOE) which considers both the energy generation benefits and investment costs is introduced to the economic evaluation of different structures of LPPs.